Is vervolging inherent in die Rooms-Katolieke stelsel? - Pretorius, C. v. N.(Christiaan van Niekerk),1928- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B.D.) -- Universiteit van Stellenbosch, 1951.